Frações orgânicas e mineral na produção de mudas de mamoeiro CV. THB - Paixão, Marcus Vinicius Sandoval (2012)
The objective of this study was to evaluate the effect of chicken manure associated with superphosphate fertilizer in the production of papaya cv THB. The experiment was conducted in a nursery farm in Linhares-ES, in a randomized block design, factorial scheme with additional control, with four replications, with trays distributed in tubes with a capacity of 50 cm3 containing substrado Bioplant ®. The factors were chicken manure and superphosphate levels: five levels of chicken manure (0, 10, 20, 30, 40% v / vt) x five levels of superphosphate (0, 5, 10, 15, 20 Kg m-3) with an additional control, the standard mixture used in the region with the fertilizer Basacote ® at a dose of 10 kg m-3. Was evaluated the percentage of emergence (PE), the emergence speed index (ESI), the mean emergence time (MET), the rate of chlorophyll content, height of seedlings, stem diameter, leaf number, root length, dry mass of roots and shoots. It was found that alternative treatments have improved only the ESI did not affect EP, and for the other variables are presented below the standard. Thus, it is not recommended the use of chicken manure in the production of seedlings of papaya cv. THB. Also not recommended the addition of superphosphate to the standard substrate.